Taxes on Tax‐Exempt Bonds - ANG, ANDREW; BHANSALI, VINEER; XING, YUHANG (Journal of Finance, 2010)
ABSTRACT Implicit tax rates priced in the cross section of municipal bonds are approximately two to three times as high as statutory income tax rates, with implicit tax rates close to 100% using retail trades and above 70% for interdealer trades. These implied tax rates can be identified because a portion of secondary market municipal bond trades involves income taxes. After valuing the tax payments, market discount bonds, which carry income tax liabilities, trade at yields around 25 basis points higher than comparable municipal bonds not subject to any taxes. The high sensitivities of municipal bond prices to tax rates can be traced to individual retail traders dominating dealers and other institutions.